How the timing of visual feedback influences goal-directed arm movements: delays and presentation rates - Eli Brenner; Chris A. G. van Straaten; A. Julia de Vries; Tobias R. D. Baas; Kirsten M. Bröring; Jeroen B. J. Smeets (Experimental Brain Research, 2023)
Visual feedback normally helps guide movements to their goal. When moving one’s hand, such guidance has to deal with a sensorimotor delay of about 100 ms. When moving a cursor, it also has to deal with a delay of tens of milliseconds that arises between the hand moving the mouse and the cursor moving on the screen. Moreover, the cursor is presented at a certain rate, so only positions corresponding with the position of the mouse at certain moments are presented. How does the additional delay and the rate at which cursor positions are updated influence how well the cursor can be guided to the goal? We asked participants to move a cursor to consecutive targets as quickly as they could. They did so for various additional delays and presentation rates. It took longer for the mouse to reach the target when the additional delay was longer. It also took longer when a lower presentation rate was achieved by not presenting the cursor all the time. The fraction of the time during which the cursor was present was more important than the rate at which the cursor’s position was updated. We conclude that the way human arm movements are guided benefits from continuous access to recent visual feedback.